USING FILM SOCIETIES IN HUMAN RIGHTS EDUCATION: A CASE STUDY IN AN UNDERGRADUATED COURSE IN INTERNATIONAL RELATIONS IN BRAZILA UTILIZAÇÃO DE CINECLUBES NA EDUCAÇÃO EM DIREITOS HUMANOS: UM ESTUDO DE CASO ENVOLVENDO UM CURSO DE RELAÇÕES INTERNACIONAIS NO BRASIL - Marchiori Neto (FURG/RS), Daniel Lena; Ferreira (FURG/RS), Luciano Vaz (Caderno de Relações Internacionais, 2017)
This paper aims to evaluate film society as a didactic instrument of human rights education in an undergraduate course in International Relations in Brazil. Based on a case study carried out at the Federal University of Rio Grande (FURG), film society is taken as a very efficient way of arousing students' interest in human rights when properly planned, especially in a traditionally elitist career focused on issues such as international trade and negotiation. On the one hand, film exhibition captures attention of stu-dents and induces an exercise of alterity. Therefore, it is a useful activity to deal with the complexity of human rights. In addition, debates and dis-cussions held after films exhibitions proved to be a privileged space, both to consolidate the importance of theme and also to encourage the reading of indicated bibliography.